Effective Professors: An Insight into their Philosophy and Practice - Joseph, Stephen - (Advances in Social Sciences Research Journal, 2018)
This qualitative study investigated the philosophy and practice of effective professors in the Trinidad and Tobago education system. A purposive sampling method was employed, utilizing standardized, open-ended student interviews as the data collection method for the study. Data analysis consisted of examining, categorizing, and tabulating the evidence to address two research questions of the study. Three themes emerged from the study, namely, getting to know students; teacher as life-long learner; and teacher as role model. Findings of the study revealed that most of the participants believe that getting to know students is an important element in their teaching, while others embrace the idea of life-long learning as an essential requirement for a successful practice. Some professors in the study hold a somewhat idealist philosophy and focus on modelling positive behaviours for students to emulate. While the results of this study cannot be generalized to the larger population of teachers in Trinidad and Tobago, the study is important because it provides an insight into the different philosophic positions of professors. It also introduces the conversation of how effective teachers conduct their practice in the context of the Trinidad and Tobago education system.